1875
DOI: 10.1144/gsl.jgs.1875.031.01-04.49
|View full text |Cite
|
Sign up to set email alerts
|

Descriptions of the Graptolites of the Arenig and Llandeilo Rocks of St. David's

Abstract: I n the neighbourhood of St. David's, the Arenig rocks, described by Mr. Hicks in his paper read at the last meeting of the Geological Society*, are the earliest in which Graptolites are known to occur; and yet, when once they appear, so diversified are their forms that these Pembrokeshire rocks are only equalled, in the number and variety of the genera they contain, by the Canadian Graptolite-bearing rocks of equivalent age known as the Quebec Group. In more ancient deposits two specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
2

Year Published

1963
1963
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(19 citation statements)
references
References 0 publications
0
17
0
2
Order By: Relevance
“…13 for biserials). Order Graptoloidea Lapworth in Hopkinson & Lapworth, 1875, emend. Fortey & Cooper, 1986Suborder Axonophora Frech, 1897, emend.…”
Section: Systematic Partmentioning
confidence: 99%
“…13 for biserials). Order Graptoloidea Lapworth in Hopkinson & Lapworth, 1875, emend. Fortey & Cooper, 1986Suborder Axonophora Frech, 1897, emend.…”
Section: Systematic Partmentioning
confidence: 99%
“…The specimens had previously been identified as Amplexograptus confertus (Lapworth) (Hopkinson and Lapworth, 1875) but further study of the unsectioned specimens showed that these specimens differed considerably from that form and could not be assigned to any other described species. I wish to thank Professor O. M. B. Bulman for all the help and advice he has given me throughout this work and for passing on the material.…”
Section: Introductionmentioning
confidence: 98%
“…Yin & Lu (1936-1937 collected fossils from, and described, the Jenhochiao section (now called the Banpo section) of Shihtien (now called Shidian). They reported the discovery of an Ordovician graptolite fauna including specimens they identified as Didymograptus nanus Lapworth in Hopkinson & Lapworth, 1875, Didymograptus sp. indet., Dictyonema sp.…”
mentioning
confidence: 99%